Phycoremediation of wastewater using algal-bacterial photobioreactor: Effect of nutrient load and light intensity. (September 2019) - Ashok, Vaishali; Shriwastav, Amritanshu; Bose, Purnendu; Gupta, Sanjay Kumar
Abstract: The current study demonstrates the nutrient removal efficiency of algal-bacterial photobioreactors in the semi-batch mode for secondary treated domestic wastewater. The experiments were conducted to predict the optimum conditions for running a photobioreactor at a comparatively larger scale. The main focus was on optimizing illumination costs and nutrient removal efficiency to make reactor construction and operation economically viable. Chlorella vulgaris and Chlamydomonas reinhardtii were used for the experiments. Various input parameters were varied, and nutrient removal efficiencies along with biomass, chlorophyll-a content, temperature, pH, alkalinity, dissolved organic carbon, and dissolved oxygen were monitored. Model simulations were also run to confirm optimum performance. A maximum of 25 mg l −1 N and 10 mg l −1 P were found to be efficiently removed within 2 days hydraulic retention time (HRT), 9 h:3 h light: dark condition and 1543 μmol photons m 2 s −1 light intensity. The results demonstrate superior nutrient removal efficiency than similar to previous studies. Graphical abstract: Unlabelled Image Highlights: Nutrient removal efficiency of algal-bacterial photobioreactors was demonstrated. Optimum conditions for running a photobioreactor at pilot scale were assessed. Nutrient removal and biomass production at varying conditions were monitored. Optimum nutrient removal notice at 9 h:3 h light: dark, & 1543 μmol photons m 2 s −1 . Maximum 25 mg l −1 N and 10 mg l −1 P were efficiently removed within 2 days HRT.